FOUNDATION AND DESCRIPTION OF INFORMATIONAL AND PSYCHOLOGICAL DESTRUCTIVE NATURE INFLUENCES DYNAMICS MODEL IN SOCIAL NETWORKS - V. A. Minaev; S. V. Dvoryankin (Безопасность информационных технологий, 2016)
The article provides a definition of information and psychological technologies and the main channels of information and psychological influences (IPI) on social groups. A detailed analysis of the modeling human behavior experience, including the work of Soviet, Russian and foreign scientists is given. It is concluded that mathematical models of information-psychological dynamics influence on the current stage of psychological science development perspective only in relation to mass consciousness. Due to the complexity and poor knowledge of processes occurring in the human psyche and determined his personal peculiarities, the creation of adequate mathematical models of IPI in the individual consciousness is impossible, but for the expert prediction and assessment of the IPI dynamics on a particular member of a social group should use existing proven scientific tests and technique. It has been shown that a significant improvement in the predictability of mathematical models expected in the transition to a dynamic model in the state space. Given verbal and formal description of the model, leading to a form of non-linear differential equation describing the diffusion of innovations. The models take into account of the mass media influence on society, interpersonal information exchange, the effect of forgetting influence. It was emphasized that similar modified mathematical model has given good results in its application to the description of the electoral processes in Russia and spread of ideas of the "Arabian Spring" through social networks.